Hello“Fake”, Goodbye “Real”: a study of the motivations of Chinese consumers to purchase counterfeits - Du, Qi (2013)
ABSTRACT Purpose: This research focuses on studying the underpinning motivations of Chinese consumers to participate in the consumption of counterfeits. Design/methodology/approach: A total of 15 in-depth interviews were conducted with the Chinese consumers who have experience of knowingly purchasing counterfeit and live in Zhejiang province and Shanghai with age from 20 to 35. Findings: The findings show ten major motivations which facilitate Chinese consumers to purchase counterfeits:first, price premium; second, guaranteed quality; third, fashion and design; fourth, self-image; fifth, low perceived risk; sixth, having fun and joy; seventh, face; eighth, social conformability; ninth, reference group and the final one, trusted retailers. Practice implications: The research provides an in-depth understanding of Chinese consumers’ motivations to purchase counterfeits. The research findings can be used to formulate political, legal and marketing strategies to help fight against counterfeiting in China. Research limitation: The findings are limited to the Chinese consumers in Zhejiang province and Shanghai, which lacks the generalization and transferability to the whole China and other International market. Also, the sample is small and biased. Moreover, the researcher’ reflexivity fails to contribute to the objectivity of the research. Originality/value: Previous studies tend to focus on specific product category or product and heavily rely on quantitative research method, whereas this research focuses on various counterfeits and adopts qualitative research method. Furthermore, it is specific in the China context. Keyword Counterfeiting, Consumers, Motivations, China